Balance of Payments Manual. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The fifth edition of Balance of Payments Manual, issued in 1993, presents revised and updated standards for concepts, definitions, classifications, and conventions for compilation of balance of payments and international investment position statistics that reflect the widespread changes that have taken place in international transactions since the fouth edition was published in 1977. As the international standard, the Manual serves as a guide for IMF member countries that regularly report balance of payments data to the IMF. The Manual contains significantly expanded and restructured coverage of financial flows and stocks and international transactions in services. Harmonization with the System of National Accounts and other IMF statistical systems is also greatly increased. See also companion volumes, the Balance of Payments Compilation Guide and the Balance of Payments Textbook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet